2022
DOI: 10.21037/jtd-22-782
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia defined by skeletal muscle mass index at the third lumbar vertebra is a prognostic factor for extensive-stage small cell lung cancer patients: a retrospective study

Abstract: Background: Small cell lung cancer (SCLC) is one of the most aggressive types of lung cancer and reliable indicators are needed for improved patient management. The evaluation of skeletal muscle index of the third lumbar vertebra (L3MI) based on computed tomography (CT) is used to estimate patient prognosis in multiple cancers. However, its function in extensive-stage SCLC remains controversial. Considering that the maintenance of muscle mass may affect the survival of cancer patients. Herein, a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Systemic inflammation promotes tumor progression through diverse mechanisms, such as angiogenesis, immune response suppression, and epithelial‐mesenchymal transition 41–43 . NLR and PMI each may reflect different aspects of the inflammatory process and have been suggested to be prognostic factors in SCLC 3,6,20,44–46 . The combined model integrating novel and conventional markers related to systemic inflammation may provide a more comprehensive assessment of the inflammatory status and its potential impact on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic inflammation promotes tumor progression through diverse mechanisms, such as angiogenesis, immune response suppression, and epithelial‐mesenchymal transition 41–43 . NLR and PMI each may reflect different aspects of the inflammatory process and have been suggested to be prognostic factors in SCLC 3,6,20,44–46 . The combined model integrating novel and conventional markers related to systemic inflammation may provide a more comprehensive assessment of the inflammatory status and its potential impact on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 , 43 NLR and PMI each may reflect different aspects of the inflammatory process and have been suggested to be prognostic factors in SCLC. 3 , 6 , 20 , 44 , 45 , 46 The combined model integrating novel and conventional markers related to systemic inflammation may provide a more comprehensive assessment of the inflammatory status and its potential impact on tumor progression. This approach is also supported by previous studies that have demonstrated the value of combining multiple inflammatory markers to improve prognostic stratification in patients with SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proposed the use of L3 vertebral level SMI as a surrogate marker for sarcopenia and frailty [ 29 , 34 , 35 ]. However, other studies have used total cross-sectional muscle area L1 [ 36 ], psoas muscle area specifically at the level of the umbilicus [ 37 ], lower pectoralis muscle area [ 38 ], and paraspinal muscle index [ 39 ] as markers of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] The relapse rate of SCLC after first-line treatment is certainly high and it is believed that the current staging system is not sufficient to accurately evaluate survival of SCLC patients. [9,10] Therefore, a lot of indicators which might contribute to the prediction of survival of SCLC patients have been reported in the last several years such as the sarcopenia [11] and lung immune prognostic index (LIPI). [12] However, these indexes are limited in clinics due to the inconvenience and low efficiency.…”
Section: Introductionmentioning
confidence: 99%